Can the Intermittent Training Generate Alterations on the Liver Tissue of Rats Submitted to a Hyperlipidic Diet? - Barbosa Magalhaes, Alan Jose [UNESP]; Castoldi, Robson Chacon; Trindade Camargo, Regina Celi [UNESP]; Tamura Ozaki, Guilherme Akio [UNESP]; Costalonga, Regiane Rocha [UNESP]; Moreira, Rafael Junges [UNESP]; Seraphim, Patricia Monteiro [UNESP]; Silva Camargo Filho, Jose Carlos [UNESP] (Soc Chilena Anatomia, 2016)
Studies indicate that increasing physical activity and decreasing levels of fat in the liver help to decrease the risk of morbidity from liver conditions. This study aimed to evaluate the effects of an eight week intermittent training program on the liver tissue of rats subjected to a hyperlipidic diet. The study consisted of 30 male Wistar rats, divided into the following groups: Sedentary Control (SC) Exercise Control (EC) (fed on standard feed and water) Sedentary Obese (SO) and Exercise Obese (EO) (fed on bacon, ham, sausage, biscuits, soda and standard feed), which performed intermittent training through electrically stimulated jumps, with three sets of 12 repetitions, three times per week for eight weeks. At the end of the training period, the animals were euthanized, and their livers removed for histological processing and hematoxylin and eosin staining (HE). Soon afterwards, caryometric analysis of the hepatocyte nuclei was performed. From the presented results it can be seen that the hepatocyte nuclei of the obese animals were smaller in relation to those of the control animals, therefore, exercise combined with an appropriate diet proved to be efficient in not causing alterations in the hepatocyte nuclei, conserving normal cell function and reducing the chances of the appearance of tissue damage. Furthermore, exercise in isolation cannot be considered a protective factor against the alteration of the liver cells.
Keywords: High fat diet; Exercise; Hepatocytes